Aerosol-jet printed flexible organic photodiodes: semi-transparent, color neutral, and highly efficient - Eckstein, Ralph; Rödlmeier, Tobias; Glaser, Tobias; Valouch, Sebastian; Mauer, Ralf; Lemmer, Uli; Hernandez‐Sosa, Gerardo (Advanced electronic materials, 2015)
Fully aerosol-printed flexible semitransparent organic photodiodes (OPDs) are presented that have specific detections >1 × 1011 Jones from 400 to 750 nm, spectral response of 0.26 A W−1, and bandwidths up to 300 kHz. The devices are prepared in an inverted architecture without the use of indium tin oxide (ITO) or fabrication processes besides aerosol printing. The OPDs show semitransparency with excellent color neutrality.
Gesehen am 09.07.2020